Los estudios irlandeses en España 2022 - Teresa Caneda-Cabrera (Estudios Irlandeses, 2023)
If 2022 marked the end of a full decade of centenary commemorations in Ireland, it also marked the beginning of what Public Health agencies around the world proclaimed as a gradual “return to normal”. Thus, whereas we continued learning to live with COVID-19 during the past year, we also witnessed with relief how many of the restrictions affecting international mobility were finally removed as schools, businesses, indoor activities and leisure travel resumed. Against the background of the previously cancelled 19th annual meeting of 2020, which was later held online in 2021, the year 2022 was a memorable one for Irish Studies in Spain. At a time when the world gradually began to reopen, AEDEI members successfully managed to gather in person again on the special occasion of the 20th International AEDEI Conference, fittingly devoted to “Ireland in Transformation (1922-2022)” and held on June 2-3 (when mask-wearing was still compulsory in many settings) in the beautiful Unesco World Heritage city of Burgos.